Janus Reactors with Highly Efficient Enzymatic CO2 Nanocascade at Air–Liquid Interface - Gao, Song; Mohammad, Munirah; Yang, Hao-Cheng; Xu, Jia; Liang, Kang; Hou, Jingwei; Chen, Vicki (ACS applied materials & interfaces, 2017)
Though enzymatic cascade reactors have been the subject of intense research over the past few years, their application is still limited by the complicated fabrication protocols, unsatisfactory stability and lack of effective reactor designs. In addition, the spatial positioning of the cascade reactor has so far not been investigated, which is of significant importance for biphase catalytic reaction systems. Inspired by the Janus properties of the lipid cellular membrane, here we show a highly efficient Janus gas–liquid reactor for CO2 hydration and conversion. Within the Janus reactor, nanocascades containing the nanoscale compartmentalized carbonic anhydrase and formic dehydrogenase were positioned at a well-defined gas–liquid interface, with a high substrate concentration gradient. The Janus reactor exhibited 2.5 times higher CO2 hydration efficiency compared with the conventional gas–liquid contactor with pristine membranes, and the formic acid conversion rate can reach approximately 90%. Through this work, we provide evidence that the spatial arrangement of the nanocascade is also crucial to efficient reactions, and the Janus reactor can be a promising candidate for the biphase catalytic reactions in environmental, biological and energy aspects.